Test results of steel nails for wooden structures - Klochko, L. (Ways to Improve Construction Efficiency, 2024)
The new standard for the design of wooden structures, which was recently introduced into the practice of design in Ukraine, contains updated modern approaches to calculation and design, including nodal nail connections. Such approaches are associated with the use of more complex calculation expressions that take into account a larger number of influencing factors. The strength of steel nails for nailed joints is among such factors. However, there are currently no available data on the strength and deformation characteristics of nails in the specialized or reference literature. In addition, these characteristics depend on the product supplier. Experimental studies remain the only reliable way to determine the mechanical characteristics of steel nails. They were conducted for nails of two diameters - 4.2 mm and 5.5 mm. The tests were performed on the UG20/2 universal machine. In the course of research, a diagram of the operation of steel under load was automatically constructed, which turned out to be not entirely characteristic of the classical diagram of carbon steel. According to the author’s assumption, the steel of the nails was previously subjected to mechanical processing in the form of slander. Quantitative values of the obtained mechanical characteristics depend somewhat on the diameter of the nail, but are generally quite stable. The yield strength is in the range of 560-650 MPa, the strength limit is in the range of 620-690 MPa, and the relative longitudinal elongation is in the range of 35-50%. It is also worth noting that the obtained mechanical characteristics based on the test results of 5 samples have a rather small spread within 10 %. This testifies to the rather high quality of steel for the manufacture of nails on the one hand, as well as to the high quality of the nail manufacturing process itself. As prospects for further research in this direction, it is recommended to expand the range of nails for testing both in terms of diameters and in terms of suppliers of these products in Ukraine.